UJI KETAHANAN TANAMAN CABAI KERITING (Capsicum annuum L.) HASIL INDUKSI MUTASI DENGAN ETHYL METHANE SULPHONATE (EMS) PADA GENERASI KEDUA TERHADAP PENYAKIT ANTRAKNOSA - FITRI, DWI RINI KURNIA (IAIN Batusangkar, 2010)
The research study about the screening of the resistance of red chilli (Capsicum annuum L.) resulted from mutation induced by Ethyl Methane Sulphonate (EMS) on the second generation (M2) to antrachnose diseases has been done by using descriptive method to intensity diseases of Colletotrichum capsici from mutant fruit of second generation. The result showed that the intensity of antrachnose on red chilli generation ranged from 23.69% to 54.82% with tolerance criteria susceptible and very susceptible.Key words: mutation induced, ethyl methane sulphonate, antraknosa red chille, antrachnose